2014
DOI: 10.1186/1550-2783-11-29
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of isoflavone supplementation and exercise restores the changes in hepatic protein expression in ovariectomized rats - a proteomics approach

Abstract: BackgroundPostmenopausal women experience adverse physiological changes caused by estrogen deprivation. Here, we hypothesized that the administration of isoflavone, a phytoestrogn, and/or physical exercise could reverse changes in the levels of hepatic enzymes disturbed by loss of estrogen to ameliorate postmenopause-related health problems.MethodsThirty-week-old female Sprague–Dawley rats were divided into five groups: a sham-operated (SHAM) group, ovariectomized groups on a regular diet with exercise (EXE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In regard to human-based research, there is evidence that soybean-based polyphenol supplementation can benefit lipid oxidation and subsequently endurance exercise performance [ 36 , 37 ] and, further, benefit CVD risk factors in menopausal women through modulating hepatic protein expression profiles [ 26 ]. Exercise, of course, is well known to improve cardiovascular disease risk in humans and rodent models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to human-based research, there is evidence that soybean-based polyphenol supplementation can benefit lipid oxidation and subsequently endurance exercise performance [ 36 , 37 ] and, further, benefit CVD risk factors in menopausal women through modulating hepatic protein expression profiles [ 26 ]. Exercise, of course, is well known to improve cardiovascular disease risk in humans and rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that a combinatory regimen of isoflavone supplementation and exercise may be beneficial to menopausal women through modulating the hepatic protein expression profile [ 26 ]. This study also indicated that the combination of an isoflavone diet and exercise was more effective in reversing changes in ovariectomy-induced hepatic protein expression than either intervention alone.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, combining genistein and exercise did not provide an additional benefit on NAFLD compared with either treatment alone. Although there were no other studies that directly evaluated the effects of these treatment on NAFLD, a proteomics study using ovariectomized rats indicated that isoflavone and exercise combination therapy could favorably modulate hepatic protein expression toward normal values than either treatment alone [36]. Given that either treatment alone was so efficacious that it almost normalized histological and biochemical changes, we hypothesized that a small added benefit from combined treatment might not be apparent in this experimental study.…”
Section: Discussionmentioning
confidence: 93%
“…2D gel tandem mass spectrometry-based proteomic methods are valuable tools for quantifying differences in protein abundance between different physical conditions or treatments [14]. Current proteomic methods allow the identification of several thousand proteins from microgram quantities of proteins in skeletal muscle, cardiomyocytes [15], adipose tissue [16], and liver [7, 17, 18]. In addition, proteomics analysis has previously been performed by several groups to determine how liver proteome profiles differ between exercise-trained and untrained individuals [18], which might provide information that could be of benefit in combating the effects of postmenopause or of nonalcoholic fatty liver disease-related loss of liver function including metabolic syndrome by promoting redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Current proteomic methods allow the identification of several thousand proteins from microgram quantities of proteins in skeletal muscle, cardiomyocytes [15], adipose tissue [16], and liver [7, 17, 18]. In addition, proteomics analysis has previously been performed by several groups to determine how liver proteome profiles differ between exercise-trained and untrained individuals [18], which might provide information that could be of benefit in combating the effects of postmenopause or of nonalcoholic fatty liver disease-related loss of liver function including metabolic syndrome by promoting redox homeostasis. However, insight into the adaptive response of liver tissue proteome signatures during aging under a variety of regular exercise challenges is still required [19].…”
Section: Introductionmentioning
confidence: 99%